Effect of hot air drying on remaining water content and total phenolic content of three morphotypes of mashua (Tropaelum tuberosum Ruíz y Pav.) - Raquel N. Veliz-Sagarvinaga (2025)
Tropaeolum tuberosum Ruíz y Pav. (mashua) is a tuber cultivated in Andean zones as Huancavelica, with traditional use in food and functional potential due to its content of bioactive compounds. Due to its short fresh shelf life, its preservation is required. Hot air drying, an alternative to solar drying, can affect the stability of these compounds depending on the temperature applied. Therefore, the objective was to evaluate the effect of temperature (50, 60, 70 and 80 °C) of hot air drying on remaining water content (Y) and total phenolic content (TPC) in three morphotypes of mashua (Zapallo, Sangre de Cristo and Negra). The tubers were washed, disinfected with sodium hypochlorite (50 ppm), cut (2.5 mm), and dried (150 g) for 16 h. Free moisture was determined in the dried samples. They were then ground (particles < 850 μm) and extracts (80% methanol, 50 mg/mL) were prepared for TPC determination. Drying temperature significantly (p < 0.05) influenced the TPC as it increased from 50 to 80 °C, and did not influence the Y. TPC ranged from 1608 ± 80.22 to 2069 ± 82.01, 1732 ± 59.43 to 2069 ± 30.32 and 5286 ± 143.74 to 7929 ± 120.48 mg gallic acid equivalent/100 g dry mashua for Zapallo, Sangre de Cristo and Negra, respectively. These results indicate that hot air drying at 60 °C can be used to obtain dried mashua of the Sangre de Cristo and Negra varieties with higher TPC, while at 80 °C the TPC for the Zapallo variety is better preserved.